Printing method of solar photovoltaic cell and preparation method of silver paste
By adopting the printing method of corrosive contact silver paste and low-solid conductive welding silver paste in the production process of N-type photovoltaic cells, the problems of high silver consumption and high cost are solved, and the silver consumption and battery cost are reduced are achieved. .
Patent Information
- Application Number
- CN202411605751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
N-type photovoltaic cells require high consumption of silver paste during the production process, which leads to high costs and affects the competitiveness of the battery.
Using a printing method including corrosive contact silver paste and low-solid conductive welding silver paste, a stable gate line is formed on the surface of the battery cell by corrosive contact silver paste, and a low-solid conductive welding silver paste is overprinted thereon to reduce the The total consumption of silver.
It effectively reduces the silver consumption of a single battery, reduces the overall cost, and improves the overall cost-effectiveness and competitiveness of the battery.
Smart Images

Figure CN119480210A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery printing, and in particular to a printing method for solar photovoltaic cells and a preparation method for silver paste. Background Art
[0002] Silver paste is a conductive paste containing silver particles. When used in the manufacture of solar photovoltaic cells, it can improve the conductivity and photoelectric conversion efficiency of the cells. At present, in addition to the silicon material of the cell itself, silver paste is the raw material with the highest non-silicon cost in the N-type photovoltaic cell. Silver paste accounts for about 58% of the overall non-silicon cost of the battery, which exceeds the cumulative value of other non-silicon costs. Unlike P-type photovoltaic cells, the production of N-type photovoltaic cells requires the use of a double-sided printing silver paste process. The average mass production silver paste consumption of N-type photovoltaic cells has increased year by year, and the cost share is relatively high, which is not conducive to the cost optimization of N-type photovoltaic cells, and the competitiveness of N-type photovoltaic cells has been affected to a certain extent. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide a printing method for solar photovoltaic cells and a method for preparing silver paste, which can reduce the silver consumption of a single cell and achieve cost reduction and efficiency improvement.
[0004] In one aspect of an embodiment of the present application, a method for printing a solar photovoltaic cell is provided, comprising: printing a corrosion contact silver paste on a surface of a cell to form a grid line;
[0005] Drying the battery cell printed with the corrosion contact silver paste;
[0006] Overprinting low-solid conductive soldering silver paste on the gate line;
[0007] The battery cell printed with the low-solid conductive soldering silver paste is sintered.
[0008] Optionally, the corrosion contact silver paste comprises organic additives, micron-sized silver powder, nano-sized silver powder, organic adhesive and glass powder, wherein:
[0009] The mass percentage of the organic additive is between 0.8% and 1.8%;
[0010] The mass percentage of the micron-sized silver powder is between 75% and 80%;
[0011] The mass percentage of the nano-scale silver powder is between 3% and 5%;
[0012] The mass percentage of the organic binder is between 10.2% and 19.2%;
[0013] The mass percentage of the glass powder is between 2% and 3%.
[0014] Optionally, the organic additive includes methacrylic acid or acrylic resin or an organosilicon additive.
[0015] Optionally, the organic binder comprises a high molecular polymer and an organic solvent, wherein:
[0016] The mass percentage of the high molecular weight polymer in the organic binder is between 10% and 12%;
[0017] The mass percentage of the organic solvent in the organic binder is between 88% and 90%.
[0018] Optionally, the organic solvent includes terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate and Span 85.
[0019] Optionally, the particle size of the glass powder is between 2 μm and 2.2 μm.
[0020] Optionally, the glass powder includes 15% to 25% Bi2O3, 8% to 12% Al2O3, 12% to 18% SiO2, 15% to 22% ZnO, 18% to 22% Sb2O5, 6% to 15% B2O3, and 15% to 25% TeO3 in percentage by mass.
[0021] Optionally, the low-solid conductive soldering silver paste comprises an organic additive, micron-sized silver powder, an organic binder and glass powder, wherein:
[0022] The mass percentage of the organic additive is between 0.5% and 1%;
[0023] The mass percentage of the micron-sized silver powder is between 45% and 50%;
[0024] The mass percentage of the organic binder is between 46% and 52.3%;
[0025] The mass percentage of the glass powder is between 2.2% and 3%.
[0026] Optionally, the organic additive comprises dimethylsiloxane.
[0027] Optionally, the organic binder comprises a high molecular polymer and an organic solvent, wherein:
[0028] The mass percentage of the high molecular weight polymer in the organic binder is between 20% and 25%;
[0029] The mass percentage of the organic solvent in the organic binder is between 75% and 80%.
[0030] Optionally, the organic solvent includes terpineol, butyl carbitol, butyl carbitol acetate and tributyl citrate.
[0031] Optionally, the particle size of the glass powder is between 2 μm and 2.5 μm.
[0032] Optionally, the glass powder includes 10% to 25% Bi2O3, 8% to 14% Al2O3, 10% to 18% SiO2, 10% to 22% ZnO, 12% to 22% Sb2O5, 8% to 15% B2O3, and 10% to 25% TeO3 in percentage by mass.
[0033] Optionally, the purity of the micron-scale and nano-scale silver powders is 99.9%.
[0034] Another aspect of the embodiment of the present application provides a method for preparing a silver paste for preparing the corrosion contact silver paste in the printing method of the above-mentioned solar photovoltaic cell, comprising: mixing and dispersing an organic binder and nano-scale silver powder and glass powder, so that the organic binder, the nano-scale silver powder and the glass powder are mixed to form a primary powder;
[0035] Adding micron-sized silver powder to the primary powder, dispersing and grinding, to obtain secondary powder;
[0036] An organic additive is added to the secondary powder, and the corrosion contact silver paste is obtained after dispersion.
[0037] Another aspect of the embodiment of the present application provides a method for preparing a silver paste for preparing a low-solid conductive soldering silver paste in the above-mentioned printing method of solar photovoltaic cells, comprising: mixing and dispersing an organic binder, micron-sized silver powder and glass powder to obtain a uniformly mixed primary powder;
[0038] An organic additive is added to the primary powder, and the low-solid conductive soldering silver paste is obtained after dispersion.
[0039] The printing method of solar photovoltaic cells and the preparation method of silver paste provided in the embodiment of the present application are as follows: first, etching contact silver paste is printed on the surface of the cell to form grid lines, and the cell printed with etching contact silver paste is dried; then, low-solid conductive welding silver paste is overprinted on the grid lines; and the cell overprinted with low-solid conductive welding silver paste is sintered. The present application adopts the printing method of two pastes, etching contact silver paste and low-solid conductive welding silver paste. The etching contact silver paste is first printed on the cell. The etching contact silver paste can corrode the silicon nitride and doping layer on the surface of the cell, so that the etching contact silver paste and the surface of the cell form good contact, which is conducive to the grid lines being stably retained on the surface of the cell; then, the low-solid conductive welding silver paste is overprinted on the grid lines formed by the etching contact silver paste, so that the cell has a good electron collection function and can be used as a welding material in the subsequent solar module section; the effects of the two silver pastes compensate each other, so that the efficiency of the printed cell remains unchanged. The silver content of low-solid conductive welding silver paste is lower, which reduces the total consumption of silver of the two silver pastes on the battery cell. The overall weight of the printed battery cell is reduced accordingly, and the overall cost is reduced, which can achieve the effect of reducing costs and increasing efficiency, and improve the overall cost performance of the printed battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 is a flow chart of the printing method of solar photovoltaic cells provided in this embodiment;
[0042] Figure 2 is a flow chart of the method for preparing the corrosion contact silver paste provided in this embodiment;
[0043] Figure 3 This is a flow chart of the preparation method of the low-solid conductive soldering silver paste provided in this embodiment. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application.
[0045] In the description of this application, it should be noted that the terms "inside", "outside", etc. indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship in which the product of the application is usually placed when in use, which is only for the convenience of describing this application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this application. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0046] It should also be noted that, unless otherwise clearly specified and limited, the terms "disposed" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0047] At present, the silver paste required for printing solar photovoltaic cells is mainly composed of 2-5 micron silver powder, nano-scale silver powder, organic adhesive and glass powder. Its metallization temperature is between 600°C and 650°C. However, the cost of silver paste for solar photovoltaic cells is relatively high.
[0048] According to industry statistics, in 2024, the average silver consumption in the mass-produced silver paste of N-type photovoltaic cells will be 85 mg / piece. The price of silver will increase from US$16 / ounce in 2016 to US$30 / ounce in 2024, while the overall price of solar panels has dropped from RMB 3 / watt to the current RMB 0.7 / watt. In order to survive, photovoltaic companies have been controlling the cost of batteries, and the cost of silver paste accounts for a large part of the overall cost. Although the silver consumption per cell has dropped from the original 100 mg to the current 85 mg, the silver consumption per cell is still relatively high for the overall price of solar panels, which is not conducive to cost control.
[0049] In view of this, in order to solve the above problems, an embodiment of the present application provides a printing method for a solar photovoltaic cell, which can be applied to solar photovoltaic cells, specifically TOPcon (Tunnel Oxide Passivating Contact) cells. TOPCon cells are solar photovoltaic cells with N-type silicon wafers as substrates.
[0050] For details, please refer to Figure 1 As shown, the method includes:
[0051] Step 100: Printing and etching contact silver paste on the surface of the cell to form a grid line.
[0052] Generally, a single crystal cell is used, and its specification can be 182.2 mm×183.75 mm. The grid lines are formed on the surface of the cell by 520 mesh screen printing, and its wet weight is 17.5 mg.
[0053] When silver paste is printed on the surface of the cell, the grid lines on the surface of the cell will be fine silver grids.
[0054] Step 101: Drying the cell printed with the corrosion contact silver paste.
[0055] After printing the corrosion contact silver paste on the battery cell, the battery cell is placed in a drying furnace for drying at a temperature of about 280 degrees Celsius.
[0056] Step 102: Overprinting low-solid conductive soldering silver paste on the gate lines.
[0057] Take the cell that has been printed with corrosion contact silver paste and dried, and start printing low-solid conductive soldering silver paste. Use 520 mesh screen printing, through precise positioning, require low-solid conductive soldering silver paste to be overprinted on the grid line of corrosion contact silver paste, wet weight 21.3mg.
[0058] By using overprinting, precise patterns can be printed at the same grid line position to ensure that there will be no offset or repeated printing, thereby improving the performance and stability of the battery cell.
[0059] Step 103: Sintering the battery cell with the overprinted low-solid conductive soldering silver paste.
[0060] The battery cell printed with low-solid conductive solder silver paste is sintered, and the sintering temperature is set at about 825°C to obtain the desired battery cell.
[0061] After sintering, the cell can be tested for electrical data to determine whether the electrical performance of the cell meets the requirements. The electrical test data include: open circuit voltage 0.7416V, short circuit current 13.937A, fill factor 85.65%, photoelectric conversion efficiency 26.58%, and total single-sided wet weight of the cell 38.8mg. The test data meets the required requirements, indicating that the printing method of this application can guarantee the performance requirements of the cell.
[0062] Therefore, the printing method of solar photovoltaic cells provided in the embodiment of the present application adopts the printing method of two pastes, namely, corrosion contact silver paste and low solid conductive welding silver paste. The corrosion contact silver paste is first printed on the cell. The corrosion contact silver paste can corrode the silicon nitride and doping layer on the surface of the cell, so that the corrosion contact silver paste and the surface of the cell form good contact, which is conducive to the stable retention of the grid line on the surface of the cell; then the low solid conductive welding silver paste is overprinted on the grid line formed by the corrosion contact silver paste, so that the cell has a good electron collection effect and is used for welding in the subsequent solar module section; the effects of the two silver pastes compensate each other, so that the efficiency of the printed cell remains unchanged. In addition, the silver content of the low solid conductive welding silver paste is low, only 46%, so that the total consumption of silver of the two silver pastes on the cell is reduced, and the total consumption of silver of the two silver pastes is reduced from 85mg / piece to 75mg / piece. The overall weight of the printed cell is reduced accordingly, and the overall cost can be reduced by 25% to 30%, which can achieve the effect of reducing costs and increasing efficiency, and improve the overall cost performance and competitiveness of the printed cell.
[0063] Further, the corrosion contact silver paste includes organic additives, micron-sized silver powder, nano-sized silver powder, organic adhesive and glass powder, wherein:
[0064] The mass percentage of organic additives is between 0.8% and 1.8%;
[0065] The mass percentage of micron-sized silver powder is between 75% and 80%;
[0066] The mass percentage of nano-scale silver powder is between 3% and 5%;
[0067] The mass percentage of the organic binder is between 10.2% and 19.2%;
[0068] The mass percentage of the glass powder is between 2% and 3%.
[0069] The above components are prepared according to their mass percentage in the corrosion contact silver paste, so that it is convenient to increase or decrease the solid content of each component during the preparation.
[0070] Each component has a certain role in the formulation of the corrosion contact silver paste. For example, organic additives can disperse and dilute the paste, so that the paste can maintain a good printing shape; because when preparing the paste, aggregation and even precipitation will occur, affecting the uniformity, quality and use effect of the paste, so organic additives effectively solve the aggregation problem and can mix the components evenly.
[0071] For example, the organic additive can be methacrylic acid, which has good weather resistance and corrosion resistance; the organic additive can also be acrylic resin, which has strong activity; or an organic silicon additive can be used as an organic additive to improve and adjust the performance of the corrosion contact silver paste. The above three organic additives can all be used to make the corrosion contact silver paste printed on the battery cell, which is beneficial to the improvement of the overall performance of the battery cell. The three organic additives are selected according to the specific needs.
[0072] Micron-sized silver powder is the conductive body of the corrosion contact silver paste, and its mass percentage can be adjusted according to customer needs.
[0073] The size of silver powder particles directly affects the conductive properties of silver paste. Generally, silver powder is spherical particles. The smaller the silver powder particles, the larger their surface area and the better the conductive properties. This is because smaller particles have a larger surface area, thus providing more contact points, reducing resistance, and thus improving conductive efficiency. This application uses 2 microns to 5 microns of silver powder for mixing.
[0074] The role of nano-scale silver powder is that there is space between micron-scale silver powder. Nano-scale silver powder can fill the space between micron-scale silver powder and play a role in reducing the resistivity of the gate line.
[0075] The purity of the above-mentioned micron-scale silver powder and nano-scale silver powder is 99.9%. The higher the purity of the two silver powders, the better the conductivity of the prepared silver paste, and thus the better the conductivity of the battery cell, which can effectively improve the utilization rate of battery power and extend the battery life.
[0076] The organic adhesive is mainly used for dispersing and printing the silver powder, and bonding the components before the glass powder is activated. The mass percentage of the organic adhesive is adjusted according to the proportion of the silver powder.
[0077] Organic adhesives can specifically include high molecular polymers and organic solvents. High molecular polymers mainly achieve a firm connection between two or more objects through the interaction between their molecular chains and the surface of the adherend, thereby improving the adhesion and bonding effect of organic adhesives. Organic solvents can adjust the viscosity of organic adhesives to achieve the best use effect, and can also make organic adhesives cure quickly and improve production efficiency.
[0078] The mass percentage of the high molecular polymer in the organic binder is between 10% and 12%; the mass percentage of the organic solvent in the organic binder is between 88% and 90%.
[0079] For example, the organic solvent includes five solvents: terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, and Span 85. The five solvents are mixed in a mass ratio of 10:20:15:15:40 to obtain the desired organic solvent.
[0080] The above five components have good solubility and stability. After being mixed with an organic solvent, the stability of the slurry can be improved, so that the prepared slurry can be used for a long time.
[0081] Glass powder is an inorganic adhesive used to achieve the bonding of silver powder and silver powder. The ratio changes according to the amount of silver powder and the change of the battery cell coating process. The particle size of the glass powder can be between 2μm and 2.2μm.
[0082] The particle size of glass powder directly affects the fluidity of the slurry. Generally speaking, glass powder with smaller particle size is easier to disperse in the slurry, thereby improving the fluidity and coating properties of the slurry.
[0083] In the example of the present application, the glass powder includes 15% to 25% Bi2O3 (bismuth trioxide), 8% to 12% AL2O3 (aluminum trioxide), 12% to 18% SiO2 (silicon dioxide), 15% to 22% ZnO (zinc oxide), 18% to 22% Sb2O5 (antimony pentoxide), 6% to 15% B2O3 (boron trioxide) and 15% to 25% TeO3 (tellurium trioxide) in percentage by mass.
[0084] The above components can be mixed together in the above proportions, melted at high temperature, and cooled and crystallized to form glass powder.
[0085] For low-solid conductive soldering silver paste, it includes organic additives, micron-sized silver powder, organic binder and glass powder, wherein:
[0086] The mass percentage of organic additives is between 0.5% and 1%;
[0087] The mass percentage of micron-sized silver powder is between 45% and 50%;
[0088] The mass percentage of the organic binder is between 46% and 52.3%;
[0089] The mass percentage of the glass powder is between 2.2% and 3%.
[0090] Unlike printed corrosion contact silver paste, the component ratio of low solid conductive soldering silver paste is different from that of printed corrosion contact silver paste; and the role of each component of low solid conductive soldering silver paste can refer to the role of each component in corrosion contact silver paste, which will not be repeated here.
[0091] It should be emphasized that the mass percentage of micron-grade silver powder as the conductive body of low-solid conductive welding silver paste is 45% to 50%. Compared with 75% to 80% of micron-grade silver powder in corrosion contact silver paste, the content of silver powder in low-solid conductive welding silver paste is much lower. In this way, the total content of silver powder in both corrosion contact silver paste and low-solid conductive welding silver paste is reduced a lot, which plays a role in reducing costs.
[0092] Specifically, in the low-solid conductive soldering silver paste, the organic additive may be dimethylsiloxane. Dimethylsiloxane can increase the conductivity of the low-solid conductive soldering silver paste, and dimethylsiloxane also plays a role of lubrication and plasticization in the low-solid conductive soldering silver paste, improving the fluidity and viscosity of the low-solid conductive soldering silver paste, making it easier to coat and shape.
[0093] The organic binder in the low solid conductive soldering silver paste includes a high molecular polymer and an organic solvent, wherein:
[0094] The mass percentage of the high molecular weight polymer in the organic binder is between 20% and 25%;
[0095] The mass percentage of the organic solvent in the organic adhesive is between 75% and 80%.
[0096] The organic solvent includes terpineol, butyl carbitol, butyl carbitol acetate, and tributyl citrate. The above four solvents are combined in a mass ratio of 20:10:30:40 to form an organic solvent.
[0097] The particle size of the glass powder in the low-solid conductive soldering silver paste is between 2 μm and 2.5 μm, which is basically consistent with the particle size of the glass powder in the printed corrosion contact silver paste.
[0098] The specific components of the glass powder in the low-solid conductive soldering silver paste are the same as those of the glass powder in the printed corrosion contact silver paste, except that the mass percentages of the two are different; for example, the glass powder in the low-solid conductive soldering silver paste includes 10% to 25% Bi2O3, 8% to 14% Al2O3, 10% to 18% SiO2, 10% to 22% ZnO, 12% to 22% Sb2O5, 8% to 15% B2O3 and 10% to 25% TeO3 by mass percentage.
[0099] By setting the above components, the corrosion contact silver paste and the low solid conductive soldering silver paste can be respectively proportioned. The difference in the components of the corrosion contact silver paste and the low solid conductive soldering silver paste is mainly set to distinguish the functions of the two silver pastes. The main function of the printed corrosion contact silver paste is to corrode the surface of the battery cell to form a stable grid line, and the low solid conductive soldering silver paste is mainly used for the subsequent welding of the solar module segment, which makes the components and mass percentages of the low solid conductive soldering silver paste and the printed corrosion contact silver paste form the above differences.
[0100] Of course, when specific requirements are different, the composition ratio of the corrosion contact silver paste and the low solid conductive welding silver paste can be adjusted according to actual needs.
[0101] For example, in one embodiment of the present application, the corrosion contact silver paste is composed of an organic additive, 2-5 micron silver powder, nano-scale silver powder, an organic binder and glass powder.
[0102] Among them, the mass percentage of each component in the corrosion contact silver paste is: polysiloxane as an organic additive accounts for 1%; 2 micron to 5 micron silver powder accounts for 75%, nano-level silver powder accounts for 3%, and the purity of micron-level and nano-level silver powder is 99.9%; glass powder accounts for 2%, and organic adhesive accounts for 19%.
[0103] The organic binder includes 10% by mass of a high molecular polymer and 90% by mass of an organic solvent. The high molecular polymer is a polymer with a low sintering residual viscoelastic modulus, such as ethyl cellulose N50; the organic solvent is composed of pinene alcohol, butyl carbitol, butyl carbitol acetate, tributyl citrate, and dodecyl alcohol ester.
[0104] The particle size of the glass powder in the corrosion contact type silver paste is 2μm~2.2μm; and the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 14% SiO2, 15% ZnO, 18% Sb2O5, 6% B2O3, and 19% TeO3 by mass percentage.
[0105] The low-solid conductive soldering silver paste is composed of organic additives, 3-6 micron silver powder, organic binder and glass powder. The mass percentage of each component in the low-solid conductive soldering silver paste is as follows: organic additives account for 0.8%, 3-6 micron silver powder accounts for 46%, glass powder accounts for 2.4%, and organic binder accounts for 50.8%.
[0106] The organic additive is dimethylsiloxane, and the purity of the silver powder of 3 microns to 6 microns is 99.9%.
[0107] The organic adhesive comprises 15% by weight of a high molecular polymer and 85% by weight of an organic solvent, wherein the high molecular polymer is a polymer with a low sintering residual viscoelastic modulus, for example, the high molecular polymer may be nylon N100; and the organic solvent is composed of terpineol, butyl carbitol, butyl carbitol acetate, and tributyl citrate.
[0108] The particle size of the glass powder in the low-solid conductive welding silver paste is 2μm-2.5μm; the glass powder is obtained by sintering and crushing 18% of Bi2O3, 10% of Al2O3, 12% of SiO2, 15% of ZnO, 18% of Sb2O5, 12% of B2O3, and 15% of TeO3 in mass percentage.
[0109] The above-mentioned two types of silver pastes, corrosion contact type silver paste and low solid conductive soldering silver paste, are used for printing on battery cells. Figure 1 The printing method shown can obtain the desired battery cell.
[0110] On this basis, the present application also discloses a method for preparing silver paste, referring to Figure 2 As shown, the corrosion contact silver paste in the printing method for preparing the above-mentioned solar photovoltaic cell comprises:
[0111] Step 200: Mix and disperse the organic binder, nano-scale silver powder and glass powder to form a primary powder by mixing the organic binder, nano-scale silver powder and glass powder.
[0112] After the organic binder, nanometer-scale silver powder and glass powder are mixed, they can be mixed and stirred using a disperser, which can provide a better dispersion effect, avoid aggregation or precipitation of the mixed primary powder, and make the primary powder more uniform after mixing.
[0113] Step 201: Add micron-sized silver powder to the primary powder, disperse and grind to obtain secondary powder.
[0114] Micron-sized silver powder is added to the primary powder, the primary powder and the micron-sized silver powder are dispersed by a disperser, and the surface roughness of the mixed powder is reduced by grinding to obtain a finer secondary powder.
[0115] Step 202: adding an organic additive to the secondary powder, and dispersing the organic additive to obtain a corrosion contact silver paste.
[0116] The secondary powder is mixed with the organic additive, and dispersed and mixed by a disperser to obtain the corrosion contact silver paste of the present application.
[0117] In addition, the present invention also discloses a method for preparing silver paste. Figure 3As shown, the low-solid conductive soldering silver paste used in the printing method for preparing the above-mentioned solar photovoltaic cell comprises:
[0118] Step 300: Mix and disperse the organic binder, micron-sized silver powder and glass powder to obtain a uniformly mixed primary powder.
[0119] An organic binder, micron-sized silver powder and glass powder are mixed, dispersed and mixed by a disperser to obtain a primary powder.
[0120] Step 301: adding an organic additive to the primary powder, and dispersing the mixture to obtain a low-solid conductive soldering silver paste.
[0121] The primary powder is then mixed and dispersed with an organic additive to obtain a uniformly mixed low-solid conductive soldering silver paste.
[0122] In summary, the present application adopts the above-mentioned silver paste preparation method to prepare the corrosion contact silver paste and low solid conductive welding silver paste in the present application respectively, and these two silver pastes are applied to the battery cell according to the Figure 1 The overprinting method shown can obtain cells that can be used in the field of solar photovoltaics, and can also reduce the consumption of silver, achieve cost optimization of cells, and thus reduce the overall cost of solar modules and enhance the competitiveness of solar modules in the industry.
[0123] The preparation method of the silver paste has the same structure and beneficial effects as the printing method of the solar photovoltaic cell in the above-mentioned embodiment. The structure and beneficial effects of the printing method of the solar photovoltaic cell have been described in detail in the above-mentioned embodiment, and will not be repeated here.
[0124] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for printing a solar photovoltaic cell, characterized in that: The method comprises: Printing corrosion contact silver paste on the surface of the cell to form grid lines; Drying the battery cell printed with the corrosion contact silver paste; Overprinting low-solid conductive soldering silver paste on the grid line; The battery cell printed with the low-solid conductive soldering silver paste is sintered.
2. The method for printing solar photovoltaic cells according to claim 1, characterized in that: The corrosion contact silver paste comprises organic additives, micron-scale silver powder, nano-scale silver powder, organic adhesive and glass powder, wherein: The mass percentage of the organic additive is between 0.8% and 1.8%; The mass percentage of the micron-sized silver powder is between 75% and 80%; The mass percentage of the nano-scale silver powder is between 3% and 5%; The mass percentage of the organic binder is between 10.2% and 19.2%; The mass percentage of the glass powder is between 2% and 3%.
3. The printing method of solar photovoltaic cells according to claim 2, characterized in that: The organic additives include methacrylic acid or acrylic resin or organosilicon additives.
4. The method for printing solar photovoltaic cells according to claim 2, characterized in that: The organic binder comprises a high molecular polymer and an organic solvent, wherein: The mass percentage of the high molecular weight polymer in the organic binder is between 10% and 12%; The mass percentage of the organic solvent in the organic binder is between 88% and 90%.
5. The method for printing solar photovoltaic cells according to claim 4, characterized in that: The organic solvent includes terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate and Span 85.
6. The method for printing solar photovoltaic cells according to claim 2, characterized in that: The particle size of the glass powder is between 2 μm and 2.2 μm.
7. The method for printing a solar photovoltaic cell according to claim 2 or 6, characterized in that: The glass powder includes Bi2O3 of 15% to 25% by mass, Al2O3 of 8% to 12% by mass, SiO2 of 12% to 18% by mass, ZnO of 15% to 22% by mass, Sb2O5 of 18% to 22% by mass, B2O3 of 6% to 15% by mass, and TeO3 of 15% to 25% by mass.
8. The method for printing solar photovoltaic cells according to claim 1, characterized in that: The low-solid conductive soldering silver paste comprises an organic additive, micron-sized silver powder, an organic adhesive and glass powder, wherein: The mass percentage of the organic additive is between 0.5% and 1%; The mass percentage of the micron-sized silver powder is between 45% and 50%; The mass percentage of the organic binder is between 46% and 52.3%; The mass percentage of the glass powder is between 2.2% and 3%.
9. The method for printing solar photovoltaic cells according to claim 8, characterized in that: The organic additive includes dimethylsiloxane.
10. The method for printing solar photovoltaic cells according to claim 8, characterized in that: The organic binder comprises a high molecular polymer and an organic solvent, wherein: The mass percentage of the high molecular weight polymer in the organic binder is between 20% and 25%; The mass percentage of the organic solvent in the organic binder is between 75% and 80%.
11. The method for printing solar photovoltaic cells according to claim 10, characterized in that: The organic solvent includes terpineol, butyl carbitol, butyl carbitol acetate and tributyl citrate.
12. The method for printing solar photovoltaic cells according to claim 8, characterized in that: The particle size of the glass powder is between 2 μm and 2.5 μm.
13. The method for printing solar photovoltaic cells according to claim 8 or 12, characterized in that: The glass powder includes Bi2O3 of 10% to 25% by mass, Al2O3 of 8% to 14% by mass, SiO2 of 10% to 18% by mass, ZnO of 10% to 22% by mass, Sb2O5 of 12% to 22% by mass, B2O3 of 8% to 15% by mass, and TeO3 of 10% to 25% by mass.
14. The method for printing solar photovoltaic cells according to claim 2 or 8, characterized in that: The purity of the micron-scale and nano-scale silver powders is 99.9%.
15. A method for preparing silver paste, used for preparing the corrosion contact silver paste in the printing method of solar photovoltaic cells according to any one of claims 1 to 7 and 14, characterized in that: The method comprises: Mixing and dispersing the organic binder, the nano-scale silver powder and the glass powder to form a primary powder by mixing the organic binder, the nano-scale silver powder and the glass powder. Adding micron-sized silver powder to the primary powder, dispersing and grinding, to obtain secondary powder; An organic additive is added to the secondary powder, and the corrosion contact silver paste is obtained after dispersion.
16. A method for preparing silver paste, used for preparing low-solid conductive soldering silver paste in the printing method of solar photovoltaic cells according to any one of claims 1, 8 to 14, characterized in that: The method comprises: The organic binder, micron-sized silver powder and glass powder are mixed and dispersed to obtain a uniformly mixed primary powder; An organic additive is added to the primary powder, and the low-solid conductive soldering silver paste is obtained after dispersion.
Citation Information
Cited By
Solar cell and preparation method thereof, laminated cell and photovoltaic module
CN122349266A